Entrepreneur Voices on Company Culture. - Staff of Entrepreneur Media, Inc.; Lewis, Derek; Feifer, Jason (Irvine : Entrepreneur Press, 2018)
No longer just a buzz term, company culture has gone from something employees would like to have to something they must have. Studies show that companies who invest in their culture can see a performance increase of 20-30 percent-making it hard to overlook things like a strong and positive vision, values and beliefs that impact both employee happiness and their bottom line. With this culture-focused edition of the Entrepreneur Voices series, the staff of Entrepreneur provides an exclusive compilation of editorial articles, advice from entrepreneurs, and reflections and various culture styles
Chapter 25: When Your Company Has a "Best Butt" AwardChapter 26: When Rebel.com Needed a Culture Makeover; Chapter 27: The Easy Way to Improve Employee Engagement; Chapter 28: Publicity Stunts `"Good Culture; Chapter 29: Cutthroat Cultures Don't Work; Chapter 30: Five Signs Your Company Is Doomed; Chapter 31: Burnout Is Killing Your Growth; Chapter 32: When You Take Culture Too Far; Entrepreneur Voices Spotlight: Interview with Mikey Trafton; Part IV: Dysfunction-Reflections; Resources.
Print version record.
eBooks on EBSCOhost
Keywords: Entrepreneurship; Entrepreneurship; Entrepreneuriat; entrepreneurs; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Entrepreneurship